The influence of vertebral instability on peridural circulation and concomitant peridural fibrosis formation - BEZER, MURAT (SPRINGER, 2006)
An animal model of vertebral instability was used to analyze the effect of chronic lumbar instability on the peridural vasculature and fibrosis formation. Fifty mature male domestic rabbits were divided into five equal groups. The vertebral instability was performed by excision of supra and interspinous ligaments between L2-L3 and L3-L4, excision of transverse and spinous processes and making bilateral laminectomies and facetectomies in groups I, II, III and IV. In group V only para vertebral muscle dissection was performed without vertebral instability. The simulation of the long term effects of overuse model on unstable spines (chronic instability) were performed with the use of Electrical Neuromuscular Stimulator to simulate cyclic flexion-extension movement in groups I, II. The rabbits in group I and III were sacrified for the histological evaluation at postoperative fifth day. The rabbits in groups I II, IV and V were sacrified at postoperative 21st day. There was no peridural venous endothelial injury or stasis but there was an increased amount of polymorph nuclear leukocytes in both group I (unstable-overuse) and group III (unstable-no overuse) after sacrification at postoperative fifth day. Peridural fibrosis and also vascular changes with different grades were seen in group II, VI and V after sacrification at postoperative 21th day. The grade of the venous changes and the mean amount of peridural scar formation were prominently higher in group II (unstable-overuse) than in group IV (unstable-no overuse) and V (control group). There was no difference between group IV and V for peridural scar formation and vascular changes. In conclusion, the instability of the lumbar spine with overuse could be a cause of peridural venous circulatory impairment, resulting in fibrosis formation.
Keywords: adhesion; fibrosis; instability; peridural scar; venous dilatation; LAMINECTOMY SCAR FORMATION; LUMBAR LAMINECTOMY; ADCON-L; PREVENTION; MODEL; INHIBITION; DISKECTOMY; ADHESIONS; MEMBRANE; SPINE